Structural, Optical And Thermal Properties Of Alnb Multilayer Composite Via Stacking Method For Led Thermal Application - El Ladan, Abdulkarim Hamza (2023)
The continuous demand for light-emitting diodes (LED) is increasing as it is a retrofitting option for in-efficient incandescent, fluorescent lights (FL, CFL) and halogen lamps. However, their performance, reliability, and operational life are affected by accumulation of excessive heat within the LED, thus, the need to develop a unique, robust, and versatile low thermal resistance (Rth) solid thermal interface material (STIM) cannot be over emphasized. In this research work, AlNB nanocomposite thin films are synthesized using reactive sputtering on aluminium substrates and performance analysis (thermal/optical) of LED mounted on the grown composites is conducted. The synthesis is carried out in three different configurations named as composites (I, II and III). Composite (I) is grown based on Al and B targets with varied thickness ratios using four different (N2:Ar) gas ratios and annealing temperature (200-400°C), while composites (II and III) were based on AlN and B targets with fixed thickness ratios in three different stacking sequence at fixed gas ratio of 12:8 and annealing temperature of 400°C. The structural characterizations are studied using High-resolution X-ray diffractometer (XRD) and confirmed the presence of (225) phase of c-AlN, (216) phase of c-BN and (216) phase of c-Al structures.